Northernmost Record of Stiphodon multisquamus (Gobiiformes: Oxudercidae) Based on a Specimen from Wakayama, Japan - Kunishima, Taiga; Tanaka, Ryosuke; Hirashima, Kentarou; Maeda, Ken (Species Diversity, 2021)
One female specimen of Stiphodon multisquamus Wu and Ni, 1986 was collected from Arida-gawa River, Wakayama Prefecture, Japan, in November 2018. As the previously known range of this species was from the South China Sea, including Malaysia, Vietnam, and China, to the Ryukyu Archipelago in Japan, this specimen was reported as the first record from the Japanese mainland and the northernmost record of this species. Stiphodon multisquamus is an amphidromous fish of which pelagic larvae develop in marine habitats. It was believed that this specimen was transported from the southern region by ocean currents during the pelagic larval phase and recruited into the river in Wakayama Prefecture.